Benchmark study on glyphosate‐resistant crop systems in the United States. Economics of herbicide resistance management practices in a 5 year field‐scale study. Issue 12 (24th March 2014) - Edwards, C Blake; Jordan, David L; Owen, Michael DK; Dixon, Philip M; Young, Bryan G; Wilson, Robert G; Weller, Steven C; Shaw, David R
Abstract BACKGROUND Since the introduction of glyphosate‐resistant (GR) crops, growers have often relied on glyphosate‐only weed control programs. As a result, multiple weeds have evolved resistance to glyphosate. A 5 year study including 156 growers from Illinois, Iowa, Indiana, Nebraska, North Carolina and Mississippi in the United States was conducted to compare crop yields and net returns between grower standard weed management programs (SPs) and programs containing best management practices (BMPs) recommended by university weed scientists. The BMPs were designed to prevent or mitigate/manage evolved herbicide resistance. RESULTS Weed management costs were greater for the BMP approach in most situations, but crop yields often increased sufficiently for net returns similar to those of the less expensive SPs. This response was similar across all years, geographical regions, states, crops and tillage systems. CONCLUSIONS Herbicide use strategies that include a diversity of herbicide mechanisms of action will increase the long‐term sustainability of glyphosate‐based weed management strategies. Growers can adopt herbicide resistance BMPs with confidence that net returns will not be negatively affected in the short term and contribute to resistance management in the long term. © 2014 Society of Chemical Industry